EFFICIENCY OF THE CAREER CENTERS IN BULGARIA - Maria POPOVA‐HRISTOVA (Editura Universitatii Transilvania din Brasov, 2018)
In Western countries, the Career Center is an integral part of any university that claims to offer up‐to‐date education and services to its students.  Well‐functioning career centers are a very powerful marketing tool for attracting prospective students. The centers are at the service of both students interested in work and internship programs, as well as employers looking for prospective employees. The purpose of this study is to understand the extent to which the Bulgarian Career Centers perform correctly, their expected duties and how well they function effectively. Career Centers provide high quality services related to the career guidance and development of students. Professionally trained professionals work with learners who want to better define their interests, opportunities and potential to define the most appropriate areas for career development. Multiple techniques such as group and individual discussions, tests, and more are often used in composing such profiles.